The Implementation of Web-based Management System for Tun Fatimah Residential College - Lim, Sin Joo; NORFARADILLA BINTI WAHID (Applied Information Technology And Computer Science, 2022)
Residential College Management in Tun Fatimah (TF), Universiti of Tun Hussein Onn (UTHM) is a web-based developed system which proposed to manage various operations in residential college such as room registration, appealing process as well as reporting process. Identification of the drawbacks of the existing system leads to the designing of the computerized system that is compatible with the existing system which is more user-friendly. By having these kinds of features, the system correspondingly would be more efficient for the users. The project is developed based on the Agile in Sprint methodology. As for the implementation, the system is developed using HTML, CSS, PHP. After the testing phase, it is shown that all the functionalities are doing well as the expected outcome is the same when compared to the actual output. Besides, the user acceptance testing, proves that mostly all of the respondents are fully satisfied with the overall performance of the developed system.